Estudo dos símbolos sonoros no filme Roma, de Alfonso Cuarón - Eunice Aparecida de Faria (2024)
This research investigates how the film Roma (Roma, Mexico, 2018), directed by Alfonso Cuarón, uses sound as a symbolic strategy through the lens of Peircean semiotics. The study aims to explore the symbolic interactions and relationships between sounds and silence within the narrative, drawing on bibliographic research in semiotics, film, and music theories. The team gathered additional information from the screenplay and interviews with the film’s production team to contextualize the identified signs. The discussion covers aspects of director Alfonso Cuarón’s life and work, along with insights from sound department professionals regarding the challenges and processes they encountered during the film’s production. The production of Roma utilized two systems: Dolby Atmos by Dolby and RX by Izotope. The dissertation includes comparative analyses of Roma with Cuarón’s other works. It also features a symbolic analysis of Roma’s audio track, focusing on its dialogues, sound effects, and music. Overall, the study highlights the creative potential and significance of stylistic and technological choices in imparting meaning through sound, acknowledging the audience’s subjectivity and fostering discussions that broaden the film’s interpretive possibilities. Furthermore, the research endorses the notion that cinema’s sound has a communicative power on par with visual discourse, offering a meaning-making construct open to diverse interpretations.